2019
DOI: 10.1515/hmbci-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis: genetics of estrogen metabolism

Abstract: Background To analyze the allelic variants of genes of enzymes involved in estrogen metabolism: CYP1A1, CYP1A2, CYP19 and SULT1A1 using polymerase chain reaction-restriction fragment length polymorphism-restriction fragment length polymorphism (PCR-RFLP) analysis of women with histologically confirmed adenomyosis and women without proliferative diseases of pelvic organs was performed. We studied the following polymorphisms: CYP1A1 M1, T264 → C transition in the 3′-noncoding region; CYP1A2*1F, C734 → A transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…78 Notably, patients with adenomyosis have increased frequency of the C allele in the T/C and C/C genotypes of the CYP1A1 gene, A allele in the C/A and A/A genotypes of the CYP1A2 gene, and the T allele and C/T and C/C genotypes of the CYP19 gene compared with women without adenomyosis. 79 Additionally, COMT 158 G/A gene polymorphisms contribute to the high risk of developing adenomyosis, particularly in Asian populations. 80 These results further demonstrate the role of polymorphisms of estrogen metabolism genes in adenomyosis.…”
Section: Pathogenesis Of Adenomyosis Geneticsmentioning
confidence: 99%
“…78 Notably, patients with adenomyosis have increased frequency of the C allele in the T/C and C/C genotypes of the CYP1A1 gene, A allele in the C/A and A/A genotypes of the CYP1A2 gene, and the T allele and C/T and C/C genotypes of the CYP19 gene compared with women without adenomyosis. 79 Additionally, COMT 158 G/A gene polymorphisms contribute to the high risk of developing adenomyosis, particularly in Asian populations. 80 These results further demonstrate the role of polymorphisms of estrogen metabolism genes in adenomyosis.…”
Section: Pathogenesis Of Adenomyosis Geneticsmentioning
confidence: 99%
“…The exact mechanisms governing hyperestrogenism in adenomyosis still need to be elucidated, but genetic predisposition is suspected. One study identified differential alleles in key genes involved in estrogen metabolism in women with adenomyosis compared with the control group [ 44 ]. Aberrant expression of ERs may also be the underlying cause of dysregulated estrogen signaling in the endometrium from adenomyosis subjects, as evidenced by transcriptome analysis [ 45 ].…”
Section: Role and Causes Of Hyperestrogenism In The Pathogenesis Of Adenomyosismentioning
confidence: 99%
“…При возникновении мутации C→А в 734 положении от старта транскрипции наблюдается снижение активности фермента и соответствующего белка. Следовательно, наличие дикого аллеля определяет более высокую активность этого фермента, что может приводить к увеличению фонового уровня эстрогенов вследствие медленной скорости их окисления до неактивных продуктов метаболизма и вызывать состояние гиперэстрогенемии [4,5,7,9].…”
Section: совокупности частот генотиповunclassified
“…В последнее время увеличивается количество исследований, связанных с поиском и характеристикой полиморфных вариантов ДНК в кодирующих и некодирующих районах генов, в той или иной степени вовлеченных в канцерогенез. Эти исследования показывают, что полиморфизм ДНК даже вне кодирующей области может быть связан с ослаблением или усилением функции гена [7,8].…”
Section: Introductionunclassified